DARI DAERAH KE KAMPUS: NEGOSIASI IDENTITAS MAHASISWA - Agiva Early Wulandari; Nabila Annisa Fitri Ramadhani; Nailah Anggiraksa; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
Educational migration, where by students leave their home regions to pursue higher education, is a phenomenon of social mobility that involves not only geographical displacement but also social and cultural change. Migrant students often face a heterogeneous social environment with values, norms, and communication patterns that differ from those in their hometowns. This condition requires migrant students to undergo a process of cultural identity negotiation to interact and adapt. This study aims to understand how migrant students negotiate their identities and strategies in the face of a new social and cultural environment. This study uses a qualitative descriptive approach, collecting data through narrative questionnaires distributed online to respondents who meet the research criteria. The data obtained are analyzed descriptively and inductively by identifying similarities and differences in the respondents' experiences, then interpreting the patterns that emerge. The results of the study show that migrant students still carry their original cultural identity, which is reflected in their use of language, values of politeness, and patterns of interaction. Even so, migrant students still need to make adjustments, especially in the way they communicate, such as their choice of words, speech accents, and interaction styles. The adaptation strategies employed by migrant students include active involvement in organizations, building social relationships with peers, and maintaining support from family and religious values. This process then results in a more flexible and contextual form of identity in the form of a hybrid identity, a combination of the original cultural identity and the identity developed through interaction.